COTS silicon diodes as radiation detectors in proton and heavy charged particle radiotherapy 1 - Kaiser, Franz-Joachim; Bassler, Niels; Jäkel, Oliver (Radiation and environmental biophysics, 2010)
Modern radiotherapy facilities for cancer treatment such as the Heavy Ion Therapy Center (HIT) in Heidelberg, Germany, allow for sub-millimeter precision in dose deposition. For measurement of such dose distributions and characterization of the particle beams, detectors with high spatial resolution are necessary. Here, a detector based on the commercially available COTS photodiode (BPW-34) is presented. When applied in hadronic beams of protons and carbon ions, the detector reproduces dose distribution well, but its response decreases rapidly by radiation damage. However, for MeV photon beams, the detector exhibits a similar behavior as found in diode detectors usually applied in radiotherapy.
Gesehen am 28.02.2023